AKIBAT HUKUM PERCERAIAN TERHADAP KEDUDUKAN LAKI-LAKI DALAM PERKAWINAN NYENTANA MENURUT PERSPEKTIF HUKUM ADAT BALI (STUDI KASUS DESA PENARUKAN, KERAMBITAN, TABANAN) - Pradnyamita, Ni Made Sulistia Dwi; Ratna Artha Windari; Dantes, Komang Febrinayanti (Universitas Pendidikan Ganesha, 2024)
This study aims to determine (1) the position of sentana peperasan in inheritance right in Yeh This study aims to understand the position of men in nyentana marriages when divorce occurs from the perspective of Balinese customary law. Marriage is considered very important in any dimension, marriage can be said to be an irregular culture that develops in accordance with the times, therefore marriage is regulated by tradition, religion and state institutions. In Bali itself, there are 2 (two) types of marriage that are commonly carried out, namely ordinary marriage and nyentana marriage, where in a nyentana marriage there is a change in position between the man and the woman. In a nyentana marriage the man changes his status as a woman and the woman changes her status as a man, then when a divorce occurs in a nyentana marriage there will be the term duda mulih truna or what can be called mulih daha. Where a man who divorces in a Nyentana marriage will return to his original home without bringing any of his wife's inherited assets based on Balinese customary law, then the man who returns to his original home from a Nyentana marriage will be accepted back by his parents but will not have the position of an heir. Absolutely return to his original home and continue to carry out obligations to his original family.